Foramen oval persistente como causa de hipoxemia persistente en un paciente con neumonía grave COVID-19. Reporte de un caso - Kramer,Tomas (Sociedad Médica de Santiago, 2021)
In patients with severe COVID-19, it has been proposed as mechanism of respiratory failure, intra and extrapulmonary shunt. However, there are no reported or documented cases of this mechanism. Also, there are studies showing this mechanism is not relevant. In this report, we present the case of a patient with severe COVID-19 pneumonia, who after two months, during his rehabilitation period, presented persistent hypoxemia with orthodeoxia. Persistent oval foramen with shunt from right to left was diagnosed. The patient underwent a percutaneous closure of the defect and at 48 hours oxygen therapy could be discontinued and the patient discharged.